Influence of two-stage harvesting on the properties of cold-pressed rapeseed (Brassica napus L.) oils - Ning NING; Bing HU; Chen-yang BAI; Xiao-hua LI; Jie KUAI; Han-zi HE; Yi-lin REN; Bo WANG; Cai-hua JIA; Guang-sheng ZHOU; Si-ming ZHAO (Journal of Integrative Agriculture)
Rapeseed (Brassica napus L.) harvesting method is critical since it significantly determines the seed yield, oil quality, and industrial efficiency. This study investigated the influences of harvesting methods on the quality of cold-pressed rapeseed oil of two varieties. Oil color, peroxide value (POV), tocopherol content, fatty acid composition, and polarity of total polyphenols (PTP) contents of two rapeseed varieties in Huanggang and Xiangyang were compared through artificially simulated combined harvesting and two-stage harvesting. Results showed significant differences in the quality of rapeseed oil between the two harvesting methods. The red value (R-value), POV, total tocopherol contents, linoleic and linolenic acid content, and PTP content of the pressed rapeseed oil prepared by the combined harvesting method were about 27.6, 5.7, 15.8, 2.0, 0.5, and 28.6% lower than those of the oil produced from the two-stage harvesting method, respectively. Xiangyang and Huayouza62 performed better in the two regions and two varieties, respectively. To sum up, the rapeseed oil obtained 41–44 days after final flowering of combined harvesting, 35 days after final flowering, and six days of post-ripening of the two-stage harvesting had the best quality.